2018
DOI: 10.1109/tnsre.2018.2842464
|View full text |Cite
|
Sign up to set email alerts
|

Intersession Instability in fNIRS-Based Emotion Recognition

Abstract: Emotion recognition based on neural signals is a promising technique for the detection of patients' emotions for enhancing healthcare. However, emotion-related neural signals, such as from functional near infrared spectroscopy (fNIRS), can be affected by various psychophysiological and environmental factors. There is a paucity of literature regarding data instability and classification instability in fNIRS-based emotion recognition systems, phenomenon which may lead to user dissatisfaction and abandonment. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Therefore, in this paper, we investigated experiments between the two tasks with different difficulty levels. [31,32]. The signal mean, signal slope, signal variance, signal peak, signal kurtosis, and signal skewness were extracted as classification features.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in this paper, we investigated experiments between the two tasks with different difficulty levels. [31,32]. The signal mean, signal slope, signal variance, signal peak, signal kurtosis, and signal skewness were extracted as classification features.…”
Section: Methodsmentioning
confidence: 99%
“…To acquire brain signals resulting from mental arithmetic tasks, 16 detectors are positioned over the prefrontal cortex, in which each channel corresponds to a specific area of the prefrontal lobe. Multiple notch filters are applied to reduce physiological noises [31,32]. In the measurement process, the signal acquisition equipment is worn on the head, and the signal is transmitted to the PC through Wi-Fi.…”
Section: Fnirs Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emotion-related neural signals such as functional near-infrared spectroscopy (fNIRS) can be affected by various psychophysiological and environmental factors, resulting in data instability and classification instability, and this phenomenon can lead to dissatisfaction and abandonment of the system. In [119], the authors proposed a method to mitigate the instability of the classification in recognition of emotions based on fNIRS, using the selection of characteristics for stable characteristics. Preliminary tests showed that this method led to an improvement of approximately 5% in accuracy.…”
Section: Sensors 2020 20 X For Peer Review 15 Of 28mentioning
confidence: 99%
“…12 In recent years, fNIRS has advanced significantly and the common scalp probe has evolved into a relatively smaller and higher spatial resolution probe. 13 While fNIRS has been applied intraoperatively to study corticocortical activity in eloquent brain regions 14 and stereotactic functional localization, 11 its nonoperative applications continue to expand [15][16][17][18][19][20][21][22][23][24][25][26][27] and its value in surgical brain mapping remains limited. The present study explores the feasibility of fNIRS for intraoperative functional brain mapping using an enhanced probe and DCS for validation.…”
Section: Introductionmentioning
confidence: 99%